2000
DOI: 10.1054/bjoc.1999.1088
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of vaccination against influenza, Streptococcus pneumoniae and Haemophilus influenzae type B in patients with multiple myeloma

Abstract: Vaccination against influenza and Streptococcus pneumoniae is recommended for elderly and immunocompromised individuals. However, there is little information concerning the efficacy of vaccination in specific groups of patients. In this study, 52 patients underwent vaccination against influenza, S. pneumoniae and Haemophilus influenzae type b (Hib) as they attended hospital outpatient clinics. Serum was analysed prior to vaccination and 4–6 weeks afterwards. Antibody titres against S. pneumoniae and Hib were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(137 citation statements)
references
References 24 publications
4
130
1
2
Order By: Relevance
“…Indeed, efficacy of vaccination of myeloma patients against influenza, Streptococcus pneumoniae and Haemophilus influenza type B is poor, and only a small percentage of patients achieved protective antibodies owing to their impaired immune status. 31 Indeed, we previously determined that the average anti-MV Ab titers in myeloma patients (36.58735.99 EU/ml, n ¼ 10) were lower than in healthy individuals (100759.17 EU/ml, n ¼ 10). 11 This is an appealing feature that should favor measles virotherapy in this cohort of patients, especially as the current study demonstrates that cell-free virus can be delivered to and successfully spread in tumors at low titers of Ab.…”
Section: Virus Fold Change Treatmentmentioning
confidence: 96%
“…Indeed, efficacy of vaccination of myeloma patients against influenza, Streptococcus pneumoniae and Haemophilus influenza type B is poor, and only a small percentage of patients achieved protective antibodies owing to their impaired immune status. 31 Indeed, we previously determined that the average anti-MV Ab titers in myeloma patients (36.58735.99 EU/ml, n ¼ 10) were lower than in healthy individuals (100759.17 EU/ml, n ¼ 10). 11 This is an appealing feature that should favor measles virotherapy in this cohort of patients, especially as the current study demonstrates that cell-free virus can be delivered to and successfully spread in tumors at low titers of Ab.…”
Section: Virus Fold Change Treatmentmentioning
confidence: 96%
“…Various studies evaluating the efficacy of vaccinations in MM have demonstrated poor antibody responses [67]. Nevertheless, vaccinations against the influenza virus, S. pneumonaie and H. influenza are recommended if possible but their efficacy is not guaranteed.…”
Section: Do Avoid and Manage Infectionmentioning
confidence: 99%
“…However, patients with multiple myeloma were often unable to mount an adequate humoral response to vaccination. As many as 61 % of the patients failed to demonstrate a protective level of antibody titre even after vaccination against S. pneumoniae (Robertson et al, 2000). Thus, in recent years, the use of prophylactic intravenous immunoglobulin has been proposed.…”
Section: Discussionmentioning
confidence: 99%